Routledge handbook of religious laws - Ferrari, Silvio, 1947-; Bottoni, Rossella (London : Routledge, 2019)
Much has been written on specific religious legal systems, yet substantial comparative studies that strive to compare systems, identifying their analogies and differences, have been relatively few. This absence undermines the capacity to understand religions and becomes particularly serious when the faithful of these religions live together in the same geographical space, as happens today with increasing frequency. Both interreligious dialogue and dialogue between States and religions presuppose a set of data and information that only comparative research can provide. This book seeks to address this gap in the literature by presenting a comparative analysis of Christian, Jewish, Islamic and Hindu laws and traditions. Divided into five parts, the firstpart of the book offers the historical background for the legal analysis that is developed in the subsequent parts. Part II deals with the sources of law in the four religions under discussion. Part III addresses the dynamics of belonging and status, and Part IV looks at issues relating to the conclusion of marriage and its dissolution. The fifth and finalpart discusses how each religion views the legal other. Each part concludes with exploring what we can learn from a comparative examination of the topic that is dealt with in that part. Written by leading experts in the field, this book presents a clear and comprehensive picture of key religious legal systems along with a substantial bibliography. It provides a state of the art overview of scholarship in this area accompanied by a critical evaluation. As such, it will be an invaluable resource for all those concerned with religious legal systems, multiculturalism and comparative law.
Chapter 10: Comparative remarks: the sources of religious lawsIntroduction; Comparing Christian sources and other religious sources; Human agency and the sources of religious laws; Religious laws and the State; Conclusion; Notes; References; PART III: Dynamics of belonging and status; Chapter 11: Jewish law: dynamics of belonging and status; Introduction; Entering the religion; Leaving the religion; Rights and obligations of adherents; Further reading; Notes; References; Chapter 12: Christian law: dynamics of belonging and status; The people of God; The concept of church membership
Obsahuje bibliografie a rejstřík
Elektronická reprodukce.
Keywords: náboženské právo; právo a náboženství; srovnávací právní věda; stát a církev; religious law; religion and law; comparative law; church and state; e-knihy online; e-books online